Structure of Hybrid Interpolymeric Complexes of Polyvinyl Alcohol and Halides of Second Group Elements - I. Yu. Prosanov; E. Benassi (Advances in Materials Science and Engineering)
Density functional theory was used to investigate structure and properties of polyvinyl alcohol complexes with halides of second group elements XHal2 (X = Be, Mg, Ca, Zn, Sr, Cd, Ba, and Hg; Hal = F, Cl, Br, and I). PVA can form hybrid interpolymeric complexes with some of them. These complexes show double spiral structure of two types.